Medicoeconomic analysis of lobectomy using thoracoscopy versus thoracotomy for lung cancer: a study protocol for a multicentre randomised controlled trial (Lungsco01). Issue 6 (15th June 2017) - Pagès, Pierre-Benoit; Abou Hanna, Halim; Bertaux, Anne-Claire; Serge Aho, Ludwig Serge; Magdaleinat, Pierre; Baste, Jean-Marc; Filaire, Marc; de Latour, Richard; Assouad, Jalal; Tronc, François; Jayle, Christophe; Mouroux, Jérome; et al.
Abstract : Introduction: In the last decade, video-assisted thoracoscopic surgery (VATS) lobectomy for non-small cell lung cancer (NSCLC) has had a major effect on thoracic surgery. Retrospective series have reported benefits of VATS when compared with open thoracotomy in terms of postoperative pain, postoperative complications and length of hospital stay. However, no large randomised control trial has been conducted to assess the reality of the potential benefits of VATS lobectomy or its medicoeconomic impact. Methods and analysis: The French National Institute of Health funded Lungsco01 to determine whether VATS for lobectomy is superior to open thoracotomy for the treatment of NSCLC in terms of economic cost to society. This trial will also include an analysis of postoperative outcomes, the length of hospital stay, the quality of life, long-term survival and locoregional recurrence. The study design is a two-arm parallel randomised controlled trial comparing VATS lobectomy with lobectomy using thoracotomy for the treatment of NSCLC. Patients will be eligible if they have proven or suspected lung cancer which could be treated by lobectomy. Patients will be randomised via an independent service. All patients will be monitored according to standard thoracic surgical practices. All patients will be evaluated at day 1, day 30, month 3, month 6, month 12 and then every year for 2 years thereafter. The recruitment target is 600 patients. Ethics and dissemination: The protocol has been approved by the French National Research Ethics Committee (CPP Est I: 09/06/2015) and the French Medicines Agency (09/06/2015). Results will be presented at national and international meetings and conferences and published in peer-reviewed journals. Trial registration number: NCT02502318.